Prevalence of crack cocaine use and its associated factors in patients treated in a specialized outpatient service - Sara Silva Fernandes; Cristiane Barros Marcos; Priscila Arruda da Silva; Samuel Carvalho Dumith (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2021)
Abstract Background Despite the advance in studies addressing the use of crack cocaine, knowledge about the characteristics of users that seek treatment in the different modalities of care for substance use disorders is important to plan the operationalization of these services. Objective To analyze the prevalence and factors associated with the use of crack cocaine in outpatients. Method Cross-sectional study consisting in the analysis of the medical records of outpatients of a chemical dependency clinic located in the south of Brazil from 1999 to 2015. The Fisher's exact test and the Poisson regression model were used to analyze the data. Results Medical records from 1,253 patients were analyzed, and 1,196 (95.5%) of them contained information on the use of crack cocaine. Use of this substance was reported by 47% (95% CI [44, 50]) of the outpatients. The risk group was composed of adults aged 20-39 years, with no income, who had three or more children, did not consume alcohol or marijuana, had continuous family assistance, spontaneously looked for the service, and had already been hospitalized or assisted at a therapeutic community or psychosocial center. Conclusion There is great demand for the outpatient care of crack cocaine users. It is crucial that the risk factors guide treatment planning.